MEMBANGKITKAN SEMANGAT UMAT ISLAM - Hartono Hartono (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2020)
The resurrection people of prophet Muhammad Saw is a God mercy to all nature. Therefore, the treatiseis considered as a resurrection to humanity. With the treatise of humanity, people rose from ignoranceto a civilized life.